2020
DOI: 10.1186/s40635-020-00360-w
|View full text |Cite
|
Sign up to set email alerts
|

Flow-controlled ventilation during EVLP improves oxygenation and preserves alveolar recruitment

Abstract: Background Ex vivo lung perfusion (EVLP) is a widespread accepted platform for preservation and evaluation of donor lungs prior to lung transplantation (LTx). Standard lungs are ventilated using volume-controlled ventilation (VCV). We investigated the effects of flow-controlled ventilation (FCV) in a large animal EVLP model. Fourteen porcine lungs were mounted on EVLP after a warm ischemic interval of 2 h and randomized in two groups (n = 7/group). In VCV, 7 grafts were conventionally ventilated and in FCV, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Furthermore, FCV has been used for preservation of donor lungs during ex vivo lung perfusion (EVLP). FCV led to improved oxygenation and alveolar recruitment compared with VCV, with a higher proportion of well-aerated and less atelectatic lung areas [ 46 ]. Therefore, FCV may be a potential strategy to prolong EVLP over time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FCV has been used for preservation of donor lungs during ex vivo lung perfusion (EVLP). FCV led to improved oxygenation and alveolar recruitment compared with VCV, with a higher proportion of well-aerated and less atelectatic lung areas [ 46 ]. Therefore, FCV may be a potential strategy to prolong EVLP over time.…”
Section: Discussionmentioning
confidence: 99%
“…MVe settings impact PGD development, most likely through volu- and atelectrauma. FCV improved oxygenation, lung compliance and wet-to-dry ratio ( 88 90 ). NPV reduces secretion of pro-inflammatory cytokines and PGD rates in clinical studies ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…show that in a porcine EVLP model, FCV provides significantly better oxygenation and improved lung compliance in a larger area of ventilated lung tissue. Despite these superior functional results, total lung injury did not differ in comparison to volume controlled ventilation ( 90 ).…”
Section: Evlp Methodology and Optimizationmentioning
confidence: 96%
“…For example, Ali et al 121 recently demonstrated that with repeated EVLP and cold ischemic preservation, they could extend total preservation time to 3 d. Other experiments have demonstrated that EVLP time can be extended by modifying aspects of EVLP protocols such as ventilator settings, perfusate composition, perfusion flow, temperature, and supplemented nutrients. [122][123][124][125][126][127][128] If this concept of extended EVLP for prolonged graft preservation can be successfully demonstrated in clinical EVLP, it would be absolutely advantageous for broader graft sharing. Additionally, acutely damaged lungs, for example, from an active infection, aspiration, or traumatic injury, raise substantial concerns for favorable transplant outcomes and cannot be used for transplant currently.…”
Section: The Next Generation: Approaches Under Investigationmentioning
confidence: 99%